Preparing Mass Communications Students for an Evolving Industry: The Influence of Emotional Intelligence and Extracurricular Involvement on Career Adaptability. (March 2021) - LaGree, Danielle; Tefertiller, Alec; Olsen, Katie
Career paths of entry-level professionals in media fields are more ambiguous and complex than ever before. To make a successful transition into their careers, graduates must possess career management skills; they should be career adaptable. Grounded in a social psychological approach, a survey of college students ( N = 320) examined how emotional intelligence and extracurricular involvement influences career adaptability. Journalism and mass communications students were compared to other majors along these variables to bring insight into how career management training can be implemented. Results indicated a positive relationship between emotional intelligence and career adaptability, which was enhanced by extracurricular participation.